2011
DOI: 10.1523/jneurosci.4095-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and Prefrontal Projections to the Basal Amygdala Mediate Contextual Regulation of Fear after Extinction

Abstract: Knowing when and where to express fear is essential to survival. Recent work in fear extinction paradigms reveals that the contextual regulation of fear involves a neural network involving the hippocampus, medial prefrontal cortex and amygdala. The amygdaloid basal nuclei (BA) receive convergent input from the ventral hippocampus (VH) and prelimbic (PL) prefrontal cortex, and may integrate VH and PL input to regulate fear expression. To examine the functional organization of this neural circuit, we used cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
277
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(299 citation statements)
references
References 47 publications
(66 reference statements)
17
277
2
Order By: Relevance
“…Because the vHIPP is the primary source of contextual information to the amygdala (15) and can influence La activity indirectly via its projections to the PL (28), it is conceivable that the vHIPP contributes to the context dependence of extinction through both direct and indirect projections to the La. Indeed, it has recently been shown that BA-projecting neurons in both the PL and HIPP are preferentially active during the renewal of fear to an extinguished CS and that disconnection of either the direct or indirect routes by which the HIPP projects to the BA impaired the renewal of fear memories after extinction (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the vHIPP is the primary source of contextual information to the amygdala (15) and can influence La activity indirectly via its projections to the PL (28), it is conceivable that the vHIPP contributes to the context dependence of extinction through both direct and indirect projections to the La. Indeed, it has recently been shown that BA-projecting neurons in both the PL and HIPP are preferentially active during the renewal of fear to an extinguished CS and that disconnection of either the direct or indirect routes by which the HIPP projects to the BA impaired the renewal of fear memories after extinction (12).…”
Section: Discussionmentioning
confidence: 99%
“…There is also growing evidence for subregional differences within the PFC: the infralimbic (IL) and prelimbic (PL) cortices have opposite influences on fear expression, inhibiting and exciting amygdala output, respectively (9-11). Moreover, convergent inputs from both the PL and ventral HIPP (vHIPP) in the Ba mediate fear renewal (12). Recently, Herry et al (13) have shown that rapid transitions between behavioral states of low and high fear, evoked by fear extinction and its context-dependent renewal, respectively, can be triggered by a switch in the balance of activity between two distinct populations of Ba neurons, which appear to be integrated into discrete neuronal circuits differentially connected with the HIPP and PFC.…”
mentioning
confidence: 99%
“…Infralimbic and prelimbic cortices have opposing roles in the expression of fear following extinction learning (Senn et al, 2014), which suggests that these reciprocal connections influence the outcome of fear and extinction learning. Moreover, inputs from the ventral hippocampus onto the BLA, either directly or indirectly through the prelimbic cortex, mediate contextual control of fear and fear renewal after extinction (Orsini et al, 2011).…”
Section: Neural Systems Involved In Fear Learningmentioning
confidence: 99%
“…R. Soc. B 369: 20130160 fear renewal not only require an intact amygdala but are also hippocampus-dependent [42].…”
Section: (D) Lack Of Ophn1 Abolishes Presynaptic Long-term Potentiatimentioning
confidence: 99%